THE INFLUENCE OF COMPETENCY AND PERFORMANCE ON THE CIVIL SERVICE PROFESSIONALITY INDEX AT THE REGIONAL DEVELOPMENT PLANNING, RESEARCH, AND INNOVATION AGENCY IN BANDAR LAMPUNG CITY - Eliza, Eliza; Habiburahman, Habiburahman; Alam, Iskandar Ali (Journal of Management, Business and Social Sciences, 2024)
The professionalism of civil servants (ASN) plays a vital role in supporting government policies and national development. Enhancing the Professionalism Index of civil servants requires strengthening key factors such as competence and performance. This study aims to examine the influence of competence and performance on the Professionalism Index of civil servants at the Regional Development, Research, and Innovation Agency of Bandar Lampung City. A quantitative approach with descriptive-associative methods was applied, involving 49 civil servants as respondents. Data were collected through questionnaires measuring competence, performance, and the Professionalism Index. The analysis employed multiple linear regression. The findings reveal that competence (coefficient 0.664) and performance (coefficient 0.302) positively affect the Professionalism Index individually. Simultaneously, both factors explain 69.3% of the variation in the Professionalism Index. These results highlight that improving competence and performance significantly contributes to strengthening civil servants’ professionalism.